2020
DOI: 10.3390/pr8030273
|View full text |Cite
|
Sign up to set email alerts
|

Process Parameters Optimization of Gallic Acid Removal from Water by MIEX Resin Based on Response Surface Methodology

Abstract: In this work, the response surface methodology was used to optimize the process parameters of gallic acid adsorption on magnetic ion exchange (MIEX) resin. Based on Box-Behnken Design, a quadratic polynomial model equation including solution pH, gallic acid concentration, MIEX resin dosage and adsorption time was established. The reliability of the established regression equation was tested by variance analysis. Based on the regression equation, the technical parameters for gallic acid adsorption on MIEX resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…P -value was also used to evaluate the significance of each of the tested variables. The smaller the P-value and larger the sum of squares, the more significant the corresponding factor is [ 49 ]. Results revealed that the factors A (pH) and B (temperature) had a significant effect on paromomycin concentration ( P < 0.0001), temperature being more significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P -value was also used to evaluate the significance of each of the tested variables. The smaller the P-value and larger the sum of squares, the more significant the corresponding factor is [ 49 ]. Results revealed that the factors A (pH) and B (temperature) had a significant effect on paromomycin concentration ( P < 0.0001), temperature being more significant.…”
Section: Discussionmentioning
confidence: 99%
“…A significant interaction between 2 factors means the effect of one factor is dependent on the level of the other [ 52 ]. Contour plots can reveal the significance of the interaction between two factors: an elliptical contour implies a significant interaction between the two factors, whereas a circular contour implies that the interaction between the two factors is weak [ 49 ]. As depicted in the results, the contour plot obtained for AB was oval in shape indicating significant interaction between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…P value was also used to evaluate the signi cance of each of the tested variables. The smaller the Pvalue and larger the sum of squares, the more signi cant the corresponding factor is [56]. Results revealed that the factors A (pH) and B (temperature) had a signi cant effect on paromomycin concentration (P < 0.0001), temperature being more signi cant.…”
Section: Discussionmentioning
confidence: 95%
“…A signi cant interaction between 2 factors means the effect of one factor is dependent on the level of the other [58]. Contour plots can reveal the signi cance of the interaction between two factors: an elliptical contour implies a signi cant interaction between the two factors, whereas a circular contour implies that the interaction between the two factors is weak [56]. As depicted in the results, the contour plot obtained for AB was oval in shape indicating signi cant interaction between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller the P -value and larger the sum of squares, the more significant the corresponding factor is. 36 , 37 As shown in Table 3 , starch (A) was the most significant factor affecting antifungal production, followed by ammonium chloride (B), pH (C), temperature (D) and finally agitation (E). Temperature and pH are vital physiological parameters influencing the metabolic pathways, hence the generation of various metabolites.…”
Section: Discussionmentioning
confidence: 99%